Large-Scale Yielding Failure Prediction of Notched Ductile Plates by Means of the Linear Elastic Notch Fracture Mechanics - Torabi, A.R.; Campagnolo, A.; Berto, F. (Проблемы прочности, 2017)
The main goal of this research is to propose a failure criterion based on the linear elastic notch fracture mechanics (LENFM) for predicting tensile crack initiation from a blunt V-notch, encountering large plasticity at the notch vicinity. First, some most recently published experimental results on tensile failure of V-notched ductile aluminum plates are briefly described. Then, with the aim to avoid complex and time-consuming elastic-plastic analyses, the equivalent material concept (EMC) is employed together with a LENFM-based fracture criterion, namely the averaged strain energy density (ASED) criterion, for predicting the load-carrying capacity of the V-notched aluminum plates. A very good agreement is shown to exist between the experimental results and theoretical predictions of the EMC-ASED criterion.